The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1111/j.1365-2621.2001.tb15581.x
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrophotometric Study of Hydrogen Bonding in Methylcellulose‐based Edible Films Plasticized by Polyethylene Glycol

Abstract: With the use of Fourier Transform Infrared (FTIR) analysis applied to methylcellulose (MC) films, the hydrogen bonding formation between MC-MC molecules and between MC and a series of different-molecularweight PEGs was studied. The spectra of the films were interpreted in terms of the symmetry distortion of hydroxyl stretch at 3466.5 cm Ϫ1 , which is the measure of hydrogen bonding interactions in the polymer matrix. The symmetry distortion was determined to be affected by the MC concentration, indicating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 8 publications
(14 reference statements)
7
46
0
Order By: Relevance
“…In PEG plasticized β-Lg films phenomenal increases in permeability at high plasticizer concentrations can be attributed to the loss of cohesiveness in the film network due to increase in the number of plasticizer -plasticizer associations Previous studies have shown that PEG is an excellent plasticizer of polymers. In a study of Hydrogen Bonding in methylcellulose-based edible films plasticized by polyethylene glycol revealed that as the concentration of PEG 400 increased there was a significant increase in the hydrogen bond formation (Turhan, 2001). This result was in accordance with hypothesis that the plasticizer "solvates" polar sites on the polymer chains, especially at high plasticizer levels, thereby reducing intermolecular attraction (Martin-Polo, 1995) and increasing intermolecular spacing.…”
Section: Matrix Mobility In Maltitol / β-Lg Filmssupporting
confidence: 61%
“…In PEG plasticized β-Lg films phenomenal increases in permeability at high plasticizer concentrations can be attributed to the loss of cohesiveness in the film network due to increase in the number of plasticizer -plasticizer associations Previous studies have shown that PEG is an excellent plasticizer of polymers. In a study of Hydrogen Bonding in methylcellulose-based edible films plasticized by polyethylene glycol revealed that as the concentration of PEG 400 increased there was a significant increase in the hydrogen bond formation (Turhan, 2001). This result was in accordance with hypothesis that the plasticizer "solvates" polar sites on the polymer chains, especially at high plasticizer levels, thereby reducing intermolecular attraction (Martin-Polo, 1995) and increasing intermolecular spacing.…”
Section: Matrix Mobility In Maltitol / β-Lg Filmssupporting
confidence: 61%
“…This may be attributed to the intramolecular interaction of SA which was destroyed; then new hydrogen bonds were formed between collagen and SA. Regardless of this, some researchers have demonstrated that high viscosity makes it difficult to disperse the ingredients and eliminate visible air bubbles during the preparation of liquid films [23,32,33], leading to some discontinuities in the final films.…”
Section: Rheological Analysismentioning
confidence: 99%
“…Among the tested MC concentrations, 1.5% was the lowest concentration that could form a film. Turhan 13 reported that MC was only partially soluble above 4.0%. Consequently, 1.5% and 4.0% were selected as the minimum and maximum MC concentrations for film production.…”
Section: Mc-gly Filmsmentioning
confidence: 99%